2017
DOI: 10.37358/rc.17.1.5394
|View full text |Cite
|
Sign up to set email alerts
|

New 4-(4-Hydroxyaryl)-5-Methyl-1,3-Dithiol-2-ylidene Derivatives

Abstract: New 4-(3,5-dibromo-4-hydroxyphenyl)-5-methyl-1,3-dithiol-2-ylidene derivatives have been synthesized from the reaction of the corresponding 4-(4-hydroxyaryl)-2-N,N-dimethylamino-1,3-dithiol-2-ylium perchlorate with various methylene active compounds under basic conditions. The 1,3-dithiol-2-ylium compounds have been obtained from the reaction of the substituted a-bromo-4-hydroxypropiophenone with sodium N,N-dimethyldithiocarbamate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…[1][2][3][4] In general, charge-transfer [5][6][7][8][9][10][11][12][13][14][15] or push-pull [16][17][18][19][20] compounds have significant applications in the field of conducting materials. For these reasons heterocyclic compounds -especially those containing sulfur and nitrogen -represent an important resource for the material chemistry [21][22][23][24] and also for medicinal chemistry. [25][26][27][28][29] Important precursors for tetrathiafulvalenes are the 1,3-dithiol-2-thione derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In general, charge-transfer [5][6][7][8][9][10][11][12][13][14][15] or push-pull [16][17][18][19][20] compounds have significant applications in the field of conducting materials. For these reasons heterocyclic compounds -especially those containing sulfur and nitrogen -represent an important resource for the material chemistry [21][22][23][24] and also for medicinal chemistry. [25][26][27][28][29] Important precursors for tetrathiafulvalenes are the 1,3-dithiol-2-thione derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst these, sulfur and nitrogen-containing heterocycles receive a great deal of attention [6][7][8][9][10][11][12][13][14][15][16]. In the field of conducting materials charge-transfer [17][18][19][20][21][22] and push-pull [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] compounds have important applications. 1,3-Dithiolium derivatives have been found to exhibit an excellent biological activity, especially against gram-positive and gram-negative bacteria [39].…”
mentioning
confidence: 99%
“…Of special interest for conducting materials are charge-transfer [20][21][22][23][24][25][26][27][28][29][30] and push-pull [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] compounds. Recent studies on (1,3-dithiolium-2yl)phenolates systems revealed that 1,3-dithiolium cations can act as acceptor groups in intramolecular chargetransfer processes [27,30,48,49]. 1,3-Dithiolium systems are known for their reactivity at the C(2)-position towards nucleophiles [28].…”
mentioning
confidence: 99%